A one-pot strategy to synthesize β-ketophosphonates: silver/copper catalyzed direct oxyphosphorylation of alkynes with H-phosphonates and oxygen in the air1. Issue 18 (4th March 2015) - Chen, Xin; Li, Xu; Chen, Xiao-Lan; Qu, Ling-Bo; Chen, Jian-Yu; Sun, Kai; Liu, Zhi-Dong; Bi, Wen-Zhu; Xia, Ying-Ya; Wu, Hai-Tao; Zhao, Yu-Fen
<x xml:space="preserve">Abstract</x> A highly efficient one-pot strategy has been developed for the synthesis of β-ketophosphonates directly from alkynes and dialkyl H-phosphonates in the presence of widely available AgNO3/CuSO4 and K2S2O8 at room temperature.